pyJSON Schema Loader and JSON Editor: A tool for file-based metadata management - Nick Plathe; Markus M. Becker; Steffen Franke (SoftwareX)
This work introduces the “pyJSON Schema Loader and JSON Editor”, a client-side desktop application for offline and local environments capable of creating, editing and tracking metadata-containing JSON documents. The newly developed tool aims to support the generation and re-use of structured metadata, required for the implementation of research data management and the FAIR data principles in research workflows. pyJSON is written in Python, a modern and flexible programming language. The interface consists of a table-like view tailored to present JSON documents, enriched with information from the corresponding JSON schema. It shall assist in creating and maintaining documents containing metadata by simplifying the process of generation and editing based on a given schema. It is used to document data sets, data collections and devices in a local file structure, intending to support the transition from paper-based documentation to more modern research data management workflows, while sustaining a uniform and standardised structure, without the need to bind users to an often complex and resource demanding database system.